Radiation-Induced Alopecia after Endovascular Embolization under Fluoroscopy - Vipawee Ounsakul; Wimolsiri Iamsumang; Poonkiat Suchonwanit (Case Reports in Dermatological Medicine)
Radiation-induced alopecia after fluoroscopically guided procedures is becoming more common due to an increasing use of endovascular procedures. It is characterized by geometric shapes of nonscarring alopecia related to the area of radiation. We report a case of a 46-year-old man presenting with asymptomatic, sharply demarcated rectangular, nonscarring alopecic patch on the occipital scalp following cerebral angiography with fistula embolization under fluoroscopy. His presentations were compatible with radiation-induced alopecia. Herein, we also report a novel scalp dermoscopic finding of blue-grey dots in a target pattern around yellow dots and follicles, which we detected in the lesion of radiation-induced alopecia.